Sustainable Investment Decisions: The Role of Environmental Accounting Information in the Psychology of Gen Z Investors in Indonesia - Melsa Jumliana; Ramly; Fika Hartina Sari; Rahadian Cahyadi; Nur Asmi Ainun Kamal; Sitti Jam'iah (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the impact of Environmental Accounting Information on investment decisions and to examine the role of overconfidence—as a psychological factor—in moderating this relationship among Generation Z investors. A quantitative approach was employed, utilizing a survey method involving 80 Generation Z investors selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using linear regression and Moderated Regression Analysis (MRA) with the aid of SPSS. The results indicate that Environmental Accounting Information has a positive and significant effect on investment decisions, with a coefficient of 1.195 and a significance level of 0.000. Overconfidence also exerts a positive and significant influence on investment decisions, with a coefficient of 1.398 and a significance level of 0.000. Furthermore, the interaction between Environmental Accounting Information and overconfidence yielded a coefficient of -0.026 with a significance level of 0.003, demonstrating that overconfidence significantly weakens the impact of Environmental Accounting Information on investment decisions. These findings suggest that Generation Z investment decisions are influenced not only by available information but also by the investors' psychological characteristics in interpreting and utilizing that information. This study reinforces the behavioral finance perspective that psychological biases can influence investor responses to corporate information.